Planejamento automático de tratamento odontológico - Scaranti, Alexander; Macedo, Alessandra A. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
Limited access, inequality in the distribution of dentists, and diagnostic failures compromise oral health in Brazil. This study developed a method and a clinical decision support system integrating deep neural networks and decision logic to assist in dental treatment planning. The automatic systematization of procedures such as dental treatment planning can provide support to professionals and their formal education.